Age related macular degeneration and presence of posterior vitreous detachment - Gawęcki, Maciej; Doroszkiewicz, Mariusz; Rydzewski, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To find correlation between presence of PVD and incidence of different forms of AMD. Material and methods: 210 eyes of patients with AMD were examined. Fluorescein angiography determined type of AMD and ultrasound examination evaluated presence of PVD. Control group included 164 eyes of patients routinely admitted to the hospital for cataract surgery. Inclusion criterium was lack of AMD and retinal medical history. Results: In the control group prevalence of PVD was higher in women than in men – respectively 50.5% and 23.6%. PVD was more frequent in male patients with dry AMD (50%) than in male controls (23.6%). PVD was also more frequent in female patients with dry form of AMD (69.2%) than in controls (50.5%). In female group with AMD PVD was more frequent in patients with dry form of AMD than in patients with wet form of AMD (69.2% and 44.8%). In patients with dry AMD, PVD was statistically more frequent in women (69.2%) than in men (50%). Statistically significant was the difference between prevalence of PVD in dry and wet group (male and females together) – 60.7% in dry AMD and 42.6% in wet AMD. Conclusion: Persistence of vitreal adhesion and traction with age might lead to a shift of the dry form into wet form of AMD. Detachment of the vitreous in dry AMD might secure the persistence of dry form. Women, due to early PVD are more prone to complications resulting from vitreoretinal traction.